A study of kemp variation in the fleeces of Cheviot ewes : a thesis presented at Massey Agricultural College in partial fulfilment of the requirements for the Degree of Master of Agricultural Science in the University of New Zealand - Orwin, D F G (Massey University, 1959)
The Cheviot and its crosses are becoming increasingly important as a hill country sheep in New Zealand. The popularity of the breed is based primarily on its fertility, mothering ability and hardiness. However, its wool, which is regarded as a by-product of minor importance under the English farming system, is of greater economic value to the New Zealand farmer. The fleece of the Cheviot has been criticised by people connected with the wool trade for certain faults. Naturally, such faults lower the value of the fleece. Thus, if the return per sheep is to be maximised the fleece type would need to be improved provided that such fleece improvement does not result in lowered production in other products. Of the faults pinpointed, kempiness is one which from previous experience with Romneys, offers hope of being eliminated without undue difficulty. Observations of the Cheviot flock run at Massey Agricultural College indicated that there was great variability in kempiness at different times of the year and between sheep. Such variability in itself, suggests that kempiness may be eliminated or reduced to negligible amounts by selection of kemp-free sheep.
Keywords: Wool fibres; Cheviot sheep